Вовка Грушин и другие: рассказы / Юрий Сотник - Сотник Юрий Вячеславович (Школьная библиотека, 2008)
Экземпляры: ф. 1 (20090706) / Инвентарный номер: 93529 / Цена: 73.00 / Авт.знак: С 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6